(untitled) (Entrepreneurship Journal for Finance and Business, 2024)
This research aims to explore the modern marketing of drugs through smartphone applications, focusing on the mechanisms of reaching and influencing consumers. With the rapid technological advancement and the widespread use of smartphones, these devices have become a powerful tool exploited for illegal purposes, such as drug promotion. The research examines how drug dealers utilize modern technologies, including encryption and targeted advertising, to reach a wide audience while maintaining the confidentiality of their operations. The study reviews the digital methods employed in this field and analyzes their impact on consumer behavior from psychological and social perspectives. Additionally, the research addresses the role of applications and digital platforms in facilitating this type of illegal marketing and how personal data and artificial intelligence algorithms are exploited to attract customers. Through data analysis and a review of previous literature, the research provides a comprehensive view of the ways drug dealers adapt to the rapidly changing digital environment and how they target specific consumer groups. Ultimately, the research aims to offer practical recommendations that help develop effective strategies to reduce the impact of this type of marketing on society, emphasizing the need to strengthen digital oversight and raise public awareness of the risks of exploiting technology for illegal activities.